HUBUNGAN KEPEMIMPIN TERHADAP MOTIVASI DAN KINERJA PEGAWAI PADA CV. GRAHAAGRI INDONESIA BOGOR - Mohammad Anno Zuhrias (Sekolah Tinggi Manajemen IMMI, 2018)
CV. Graha Agri Indonesia Bogor is a field of industrial undertaking engaged in the manufacture of food type Nata de Coco. The purpose of this study is to know Relationship Leaders Against Motivation and Employee Performance CV. Graha Agri Indonesia Bogor. The methodology used in the research is, Librarian Research (Lybrary Research) and Field Research (Field Research) by conducting interviews and questionnaires to the respondents. The results obtained are:Leadership (Y) with Motivation (X1) on CV. Graha Agri Industri Bogor with calculation where t arithmetic t table that is 13,98 3,67 so Ho rejected and Ha accepted meaning with statistic test hence there is significant relation between independent variable and dependent variable.Leadership (Y) with Performance (X2) on the CV. Graha Agri Industri Bogor with the calculation where t arithmetic t table is 12.70 3.67 thus Ho is rejected and Ha accepted the meaning by statistical test then there is a significant relationship between independent variables and dependent variable.Leadership (Y) with Motivation (X1) and Performance (X2) on CV. Graha Agri Industri Bogor where F arithmetic greater than F table that is 10.66 3.67 thus can be concluded that Ho is rejected and Ha accepted means there is a strong and significant relationship between Leadership with Motivation and Employee Performance on CV. Graha Agri Industri Bogor.In doing its activities CV. Graha Agri Indonesia Bogor, is very concerned about human resources, this is the main working capital in running its activities. Human Resources need certainly needs to be developed. It can be realized through giving motivation to its employees. Motivation is one of the development process of human resource management, both for employees and for company. The planned HR development system will provide benefits for CV. Graha Agri Indonesia Bogor in the form of performance improvement, employee career, productivity improvement, which will eventually lead to increase business results and mobility of employees. Because a company is in need of employees who have quality in running the company's operational activities with satisfactory results.